Nursing care for patient Mrs. SM with a diagnosis of Broncial Asthma in the Bethesda Room, Monompia GMIBM Hospital, Kotamobagu - Mamonto , Fitrah; Jaata, Jikrun; Patonengan, Gita S.; Pongkorung , Amanda (Privietlab, 2026)
Asthma is a chronic respiratory disease that affects the airways and is commonly found in adults. The condition is characterized by bronchial hyperresponsiveness, airway inflammation, and reversible airflow obstruction triggered by various internal and external stimuli. Clinically, asthma presents with recurrent episodic symptoms such as wheezing, persistent coughing, shortness of breath, and chest tightness. These symptoms often lead to the accumulation of mucus or secretions in the respiratory tract, which can obstruct the airways and result in ineffective airway clearance. If not properly managed, this condition may worsen respiratory distress and significantly reduce the patient’s quality of life. Therefore, comprehensive nursing care is required to help maintain airway patency and improve respiratory function in patients with bronchial asthma. This study employed a descriptive case study approach to examine the nursing care provided to a patient diagnosed with bronchial asthma in the Bethesda Room at Monompia General Hospital GMIBM Kotamobagu. Data collection was conducted through patient interviews, direct observation, and physical examination to identify the patient’s clinical condition and nursing problems. The primary nursing diagnosis identified was ineffective airway clearance related to airway hypersecretion. Nursing interventions included the implementation of effective coughing exercises as a non-pharmacological therapy, patient positioning, monitoring of sputum production, and collaboration with pharmacological therapy when necessary. The results of the nursing intervention showed improvement in the patient’s airway clearance ability, indicated by increased effectiveness of coughing and reduced sputum retention. In conclusion, the application of effective coughing techniques combined with comprehensive nursing care can support airway clearance and improve respiratory comfort in patients with bronchial asthma. These findings highlight the important role of nurses in implementing non-pharmacological interventions to optimize respiratory management in clinical settings.